Co‐designing a telepractice journey map with disability customers and clinicians: Partnering with users to understand challenges from their perspective - Cloe Benz; William Scott‐Jeffs; Jerah Revitt; Chloe Brabon; Chloe Fermanis; Melanie Hawkes; Catherine Keane; Robert Dyke; Samantha Cooper; Matthew Locantro; Mai Welsh; Richard Norman; et al. (Wiley, 2024)
Abstract Introduction Telepractice has the potential to align with the directive to reduce inequalities by United Nations Sustainable Development Goal 10. Telepractice additionally addresses a national digital health strategic plan for accessible digitally enabled models of care. To plan improvements, it is essential to understand the experience of telepractice for people with disability, which may be achieved through an approach such as journey mapping. The current article provides both a disability‐specific case study and a methodological guide for the inclusion of customers and clinicians in the meaningful redevelopment of services. The Perth, Australia‐based case study aimed to gain insights into the experience of telepractice for people with disability. The methodological aim describes using co‐design to produce a journey map in collaboration with customers and clinicians, for potential replication in a wide range of health and social care contexts. Method Interview transcripts gathered from a cohort of customer participants (n = 17) were used to inform the journey map. A group of customers (n = 5) and clinicians plus one manager (n = 5) distributed the findings onto a customer experience journey map during a co‐design workshop. The journey map describes the emotional experience and actions taken, along five phases of a timeline through telepractice service interactions: (1) before, (2) selecting telepractice, (3) telepractice preparation, (4) during telepractice sessions and (5) after. Results A journey map visualisation of customer experiences was produced that identified strengths of telepractice service delivery (flexibility) while noting challenges (with technology) as opportunities for improvement. The consensus of participants was the desire to have access to telepractice currently and in the future, in addition to in‐person delivery. Conclusion These findings are valuable in the context of advocating for the incorporation of customers and clinicians through co‐design workshops in the content analysis and creation of a journey map that is representative of the lived experience of accessing telepractice services. Patient or Public Contribution The paper forms part of a larger co‐design process that included customer participants throughout the design and planning of the project, inclusion of a peer researcher and the co‐designers in the workshops, journey map and this article production.